2011
DOI: 10.3354/dao02414
|View full text |Cite
|
Sign up to set email alerts
|

Vector potential of the salmon louse Lepeophtheirus salmonis in the transmission of infectious haematopoietic necrosis virus (IHNV)

Abstract: To better understand the role of vector transmission of aquatic viruses, we established an in vivo virus−parasite challenge specifically to address (1) whether Lepeophtheirus salmonis can acquire infectious haematopoietic necrosis virus (IHNV) after water bath exposure or via parasitizing infected Atlantic salmon Salmo salar and if so, define the duration of this association and (2) whether L. salmonis can transmit IHNV to naïve Atlantic salmon and whether this transmission requires attachment to the host. Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 34 publications
0
31
0
1
Order By: Relevance
“…ref. 33). Vibrio , a genus comprising several major fish pathogens6, amongst other commensal taxa, was highly abundant in louse samples, although also present among fish and environmental samples in test and control tanks.…”
Section: Discussionmentioning
confidence: 99%
“…ref. 33). Vibrio , a genus comprising several major fish pathogens6, amongst other commensal taxa, was highly abundant in louse samples, although also present among fish and environmental samples in test and control tanks.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Jakob et al . () was conducted in parallel to the present study and they also reported dose and exposure time as key determinants of longevity of IHNV associated with L. salmonis ; however, that association was more ephemeral (12–24 h). Similarly, Oelckers et al .…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, Jakob et al . () observed successful transmission of IHNV via L. salmonis when it was able to attach to a host, but virus transmission was not detected when the parasites were confined within a fine mesh box preventing attachment. A similar experiment was conducted (using the same mesh constraint) in the present study, with similar results, but the data were not included due to low sample size associated with tank space logistic constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La tasa de mortalidad más alta (86%) se presentó en los Caligus recién extraídos de los peces portadores del virus ISA, luego con aquellos Caligus que permanecieron 12 h en el laboratorio (76% de mortalidad) y finalmente con los peces que fueron infestados con Caligus que permanecieron en el laboratorio por 48 h (45% de mortalidad). En salmón del Atlántico infestado con L. salmonis portadores de IHNV se observó que hay una mayor mortalidad de los peces a medida que la carga viral de los parásitos es mayor, ya que es retenida por más tiempo al interior del parásito (Jacob et al, 2011).…”
unclassified